138 - PERFORMANCE ANALYSIS OF FEMALE JUMPERS IN ATHLETICS (Fiep Bulletin - online, 2011)
This aims this study was to make a comparative analysis between of results to be found for jumpers in long jump, high jump, triple jump and pole vault competitions, in male youth category, of Brazilian Championship between 2000 and 2008. In order to do it, the study was grounded of results disposable in the Brazilian Confederation of Athletics (CBAT), South American Confederation (ConSulAtle) and International Association Athletic Federation (IAAF) websites, concerning the competitions in male jumpers youth category, composed for athletes with 15, 16 and 17 years. After to data analysis, we observed that, of 108 medals (Gold, Silver and Bronze) distributed of 9 years of competitions, the athletes with 17 years old was the most winners, followed by 16 years old. Despite to popularization attempt this type sports throughout Brazil, we observed that few states to stand out in athletics competitions. The results analysis of this category considered a base category, it's not optimistic, because we observed one physical performance reduction of athletes in the last years, showed this country can't have athletes of high level competitive sport in the future.
Keywords: Athletic; base category; youth championship